Differential Gene Expression in Host Ubiquitination Processes in Childhood Malarial Anemia - Anyona, Samuel B.; Raballah, Evans; Cheng, Qiuying; Hurwitz, Ivy; Ndege, Caroline; Munde, Elly; Otieno, Walter; Seidenberg, Philip D.; Schneider, Kristan A.; Lambert, Christophe G.; McMahon, Benjamin H.; Ouma, Collins; et al. (Frontiers in Genetics, 2021)
Background: Malaria remains one of the leading global causes of childhood morbidity and mortality. In holoendemic Plasmodium falciparum transmission regions, such as western Kenya, severe malarial anemia [SMA, hemoglobin (Hb) < 6.0 g/dl] is the primary form of severe disease. Ubiquitination is essential for regulating intracellular processes involved in innate and adaptive immunity. Although dysregulation in ubiquitin molecular processes is central to the pathogenesis of multiple human diseases, the expression patterns of ubiquitination genes in SMA remain unexplored. Methods: To examine the role of the ubiquitination processes in pathogenesis of SMA, differential gene expression profiles were determined in Kenyan children (n = 44, aged <48 mos) with either mild malarial anemia (MlMA; Hb ≥9.0 g/dl; n = 23) or SMA (Hb <6.0 g/dl; n = 21) using the Qiagen Human Ubiquitination Pathway RT2 Profiler PCR Array containing a set of 84 human ubiquitination genes. Results: In children with SMA, 10 genes were down-regulated (BRCC3, FBXO3, MARCH5, RFWD2, SMURF2, UBA6, UBE2A, UBE2D1, UBE2L3, UBR1), and five genes were up-regulated (MDM2, PARK2, STUB1, UBE2E3, UBE2M). Enrichment analyses revealed Ubiquitin-Proteasomal Proteolysis as the top disrupted process, along with altered sub-networks involved in proteasomal, protein, and ubiquitin-dependent catabolic processes. Conclusion: Collectively, these novel results show that protein coding genes of the ubiquitination processes are involved in the pathogenesis of SMA.